Mechanical and leakage integrity testing considerations for evaluating the performance of tissue containment systems - Herman, Alexander; Duraiswamy, Nandini; Nandy, Poulomi; Price, Veronica; Gibeily, George; Hariharan, Prasanna (Scientific reports, 2023)
Tissue containment systems (TCS) are medical devices that may be used during morcellation procedures during minimally invasive laparoscopic surgery. TCS are not new devices but their use as a potential mitigation for the spread of occult malignancy during laparoscopic power morcellation of fibroids and/or the uterus has been the subject of interest following reports of upstaging of previously undetected sarcoma in women who underwent a laparoscopic hysterectomy. Development of standardized test methods and acceptance criteria to evaluate the safety and performance of these devices will speed development, allowing for more devices to benefit patients. As a part of this study, a series of preclinical experimental bench test methods were developed to evaluate the mechanical and leakage performance of TCS that may be used in power morcellation procedures. Experimental tests were developed to evaluate mechanical integrity, e.g., tensile, burst, puncture, and penetration strengths for the TCS, and leakage integrity, e.g., dye and microbiological leakage (both acting as surrogates for blood and cancer cells) through the TCS. In addition, to evaluate both mechanical integrity and leakage integrity as a combined methodology, partial puncture and dye leakage was conducted on the TCS to evaluate the potential for leakage due to partial damage caused by surgical tools. Samples from 7 different TCSs were subjected to preclinical bench testing to evaluate leakage and mechanical performance. The performance of the TCSs varied significantly between different brands. The leakage pressure of the TCS varied between 26 and > 1293 mmHg for the 7 TCS brands. Similarly, the tensile force to failure, burst pressure, and puncture force varied between 14 and 80 MPa, 2 and 78 psi, and 2.5 N and 47 N, respectively. The mechanical failure and leakage performance of the TCS were different for homogeneous and composite TCSs. The test methods reported in this study may facilitate the development and regulatory review of these devices, may help compare TCS performance between devices, and increase provider and patient accessibility to improved tissue containment technologies.